Amplification of natural regulatory immune mechanisms for transplantation tolerance. - Chen, Z; Cobbold, S; Waldmann, H; Metcalfe, S (1996)
There is a need to derive donor-specific tolerance in clinical organ transplantation, where potential benefits remain overshadowed by chronic rejection and side effects of continual immunosuppressive therapy. It is known that the mature immune system in mice can be reprogrammed to accept a foreign graft as if it were "self." Here we show that, once generated, this state of operational tolerance becomes self-sustaining, imposing itself on new cohorts of lymphocytes as they arise. These new cohorts retain specificity for the tolerizing antigen and can be selectively amplified to tolerate new antigens that have linked expression with the original tolerogen. Regulation is critically dependent upon the continuous presence of tolerizing antigen and is mediated by the CD4+ lymphocyte population. We propose that such natural mechanisms of immune regulation may eventually be exploited for transplantation tolerance, even in fully immune-competent recipients.